Application of sodium nitroprusside results in distinct antioxidant gene expression patterns in leaves of mature and senescing Medicago truncatula plants - Fotopoulos, Vasileios; Filippou, Panagiota S.; Mylona, Photini V.; Fasoula, Dionysia A.; Ioannides, Ioannis M.; Polidoros, Alexios N.; Antoniou, Chrystalla (My University, 2014)
Sodium nitroprusside (SNP) represents one of the most commonly used NO donors in biological sciences, which acts as a signal molecule in plants responsible for the regulation of the expression of many defense-related enzymes. This study attempts to provide novel insight into the effect of application of low (100 μΜ) and high (2.5 mM) concentrations of SNP on antioxidant gene expression (cAPX, GST, FeSOD, CAT, and AOX) in mature (40 day) and senescing (65 day) Medicago truncatula plants. Quantitative real-time RT-PCR suggests that low concentration of SNP applied in mature leaves leads to an overall induction of antioxidant gene expression, while increasing concentration results in suppression of these genes. Conversely, older plants demonstrate a much more variable regulation which appears to be time dependent. The observed transcriptional regulation pattern in mature M. truncatula plants comes in support of the previously documented protective or damaging effect of SNP depending on concentration applied, whereas senescing M. truncatula plants demonstrated a general suppression in antioxidant gene expression levels regardless of SNP concentration, indicative of reduced overall plant defense capacity against free radicals.
Keywords: Sodium nitroprusside; Nitrosative stress; Oxidative stress; Antioxidants; Medicago truncatula